The challenge of unidentified decedents in Africa: The need for training and research in forensic odontology to strengthen a multidisciplinary approach - Chandler, Susan; Sudi, Stephen M.; Bailie, Keané C.; Chetty, Manogari (Frontiers in Oral Health, 2022)
Introduction The management of unidentified decedents suspected to be undocumented migrants is a growing humanitarian crisis in Africa. Identification of the dead and the right of the family to know the fate of a decedent is a fundamental human right. Forensic odontology methods can provide helpful and assisting information in the identification even in challenging low-resource settings. South Africa and other countries that are part of significant migration routes face the problem of unidentified decedents. Discussion The fundamental application of forensic odontology relies on the availability of good antemortem dental records. The state of dental records was reported to be suboptimal in South Africa and other African countries. Incorporating forensic odontology into the undergraduate training in the 23 dental schools in Africa will increase the understanding of the value of maintaining accurate dental records and potentially facilitate collaboration with dentists and forensic odontologists in cases where dental features can be used for identification. South Africa offers postgraduate training in forensic odontology, and prospects for research in Africa need to be explored. Conclusion The development of a forensic odontology career path and research prospects will provide African countries with the potential for building multidisciplinary teams to assist in solving the challenge of unidentified decedents.